Possibilities of Predicting Methotrexate-associated Toxicity in Oncohematology Based on Molecular Genetic Testing Methods - Zarui K. Simavonyan; Timur T. Valiev; Marina I. Savelyeva; Sherzod P. Abdullaev; Svetlana R. Varfolomeeva (Педиатрическая фармакология)
The development of highly effective protocols for the treatment of acute lymphoblastic leukemia (ALL) and non-Hodgkin lymphomas (NHL) followed the path of escalation of doses of cytostatic agents and improvement of supportive care. Methotrexate (MTX), used in high doses (1000–5000 mg/m2), radically changed the results of treatment of ALL and NHL in children, increasing patient survival rates. The downside of the anti-tumor effect of MTX is its organ toxicity, and therefore the development of methods for predicting the development of toxic effects of MTX is an important scientific and practical task. In recent years, the genetic factors of the patient’s organism have been considered as one of the reasons for the individual variability of pharmacokinetic and pharmacodynamic parameters of MTX. Abnormal function of folate cycle enzymes, methotrexate transporter proteins, due to gene polymorphism, may affect the effectiveness and toxicity of the drug. This review summarizes and analyzes the known genetic polymorphisms involved in MTX metabolism. The possibilities of predicting toxicity, as well as the prospects for individualizing therapy, taking into account the results of pharmacogenetic testing, are presented.